A Comparison of the Effects of Extraction and Nonextraction Orthodontic Treatments on Cephalometric Parameters and Arch Widths - Sümeyye Güler; Merve Nur Eğlenen; Mehmet Ali Yavan; Mehmet Nezir Karaca (Cumhuriyet University, 2021)
Objectives: To compare the effects of two different treatment approaches on cephalometric measurements and arch widths. Materials and Methods: The retrospective study evaluated pre- and post-treatment cephalometric radiograms and dental models of 45 patients with Class I malocclusions and moderate-severe dental tooth size arch length discrepancies that underwent extraction or nonextraction treatment between 2015 and 2020. Group I (n=22 [9 female, 13 male]; mean age, 18.0 ± 1.68 years) was treated with the Damon Q bracket system and Group II (n=23 [11 female, 12 male]; mean age, 17.9 ± 1.34 years) was treated with the conventional MBT bracket system. Pre- and post-treatment lateral cephalometric radiograms were obtained and arch widths were measured for each subject. Paired samples t-test was used to evaluate the treatment changes within each group. To compare the changes between groups, independent samples t-test was performed. Results: No significant change was detected in the sagittal and vertical skeletal parameters in both groups (p>0.05). The upper and lower incisors proclined significantly in Group I (p<0.01) and the mandibular incisors retroclined significantly in Group II (p<0.05). The lips protruded significantly and the upper lip thickness decreased significantly in Group I (p<0.01), whereas no significant difference was observed in Group II (p>0.05). All the transversal dimensions increased significantly in Group I (p<0.01), while only the intermolar distance decreased significantly in Group II (p<0.01). Conclusions: Both treatment methods provided significantly different outcomes with regard to soft tissue parameters and arch widths.